2018
DOI: 10.1016/j.molmet.2017.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Cdkn2a deficiency promotes adipose tissue browning

Abstract: ObjectivesGenome-wide association studies have reported that DNA polymorphisms at the CDKN2A locus modulate fasting glucose in human and contribute to type 2 diabetes (T2D) risk. Yet the causal relationship between this gene and defective energy homeostasis remains elusive. Here we sought to understand the contribution of Cdkn2a to metabolic homeostasis.MethodsWe first analyzed glucose and energy homeostasis from Cdkn2a-deficient mice subjected to normal or high fat diets. Subsequently Cdkn2a-deficient primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 66 publications
3
44
0
2
Order By: Relevance
“…This suggests a cell-autonomous requirement of CDKN2A to the browning process. Consistent with these findings, silencing CDKN2A expression during human iPSCs adipogenic differentiation promotes UCP1 expression and browning markers [ 60 ]. We also observed that CDKN2A expression was increased in adipocytes from obese patients.…”
Section: The Ink4a/arf Locus: a Role In Adiposementioning
confidence: 52%
See 2 more Smart Citations
“…This suggests a cell-autonomous requirement of CDKN2A to the browning process. Consistent with these findings, silencing CDKN2A expression during human iPSCs adipogenic differentiation promotes UCP1 expression and browning markers [ 60 ]. We also observed that CDKN2A expression was increased in adipocytes from obese patients.…”
Section: The Ink4a/arf Locus: a Role In Adiposementioning
confidence: 52%
“…Recently, the INK4a/ARF locus has been suggested to play a major role in the molecular switch of white-to-beige adipocyte conversion and thus is a key determinant of brown adipocyte fate ( Figure 2 ). In support of this notion, we showed that CDKN2A -deficient mice were protected against DIO exhibiting sWAT browning and increased thermogenesis and insulin sensitivity [ 60 ]. Differentiated SVF cells from sWAT displayed elevated oxidative activity with upregulation of brown fat-specific gene and increase in PKA activity and adrenergic receptor signaling pathways.…”
Section: The Ink4a/arf Locus: a Role In Adiposementioning
confidence: 87%
See 1 more Smart Citation
“…Kinome profiling to investigate biological processes is becoming easily accessible thanks to methods such as PamGene PamChip ® arrays that provide a valuable tool for direct exploration of cellular kinase activities 8,9,10 . The ability to develop bioinformatic tools to extract and analyze the data in a reproducible and robust manner is critical.…”
Section: Resultsmentioning
confidence: 99%
“…DESeq2 is an advanced methodology that analyzes comparative RNA-seq data using shrinkage estimators for fold change, standard error, and dispersion, and provides quality assessment and clustering of overdispersed data [ 54 ]. Besides accounting for non-normality and dependence of variance of RNA-seq data, DESeq2 is highly sensitive and precise for using small sample sizes, often as few as two or three replicates per experimental condition, in typical high-throughput sequencing studies [ 23 , 55 , 56 ], including the first hit [ 57 ] of the current PubMed search ( Table S1 ).…”
Section: Discussionmentioning
confidence: 99%